Investigating Global Imbalances: Empirical Evidence from a GVAR Approach - Timo Bettendorf (University of Kent, School of Economics, 2012)
This paper investigates the development of external imbalances from an international perspective by estimating a Global VAR model for the period 1981Q1-2009Q4 with a setup close to that of an international real business cycle model. The model considers 28 countries of which 10 are aggregated as the Eurozone. We compute generalized impulse response functions, as well as generalized forecast error variance decompositions, in order to measure the effects of shocks on international trade balances. The United States, Eurozone and China are considered as the sources of those shocks. We account for imbalances using real GDP, real effective exchange rates (REER) and real interest rates (RIR) as well as the oil price. Overall, we find evidence for the joint dynamics of our variables as drivers of the imbalances and relate our findings to theories of Global Imbalances. We show that real GDP is a relatively unimportant variable compared to the REER, RIR and the oil price. Moreover, we provide a counterfactual analysis of the US trade balance.
Keywords: F10; F32; F41; 330; Global Imbalances; Global VAR; International Trade; Open Economy Macroeconomics